(untitled) (CIPEEX, 2022)
Staying in a training program allows its practitioners to improve in daily activities, generating less energy expenditure to perform them, and in sports practice, executing movements with quality leads to achievements. Nowadays, where the population is increasingly busy and more exposed to technological conveniences, there is a great need for adjustments in training methods, whether for strength, aerobic, power, or flexibility [1]. Adherence to training involves an integrated balance between the mind and body, where the understanding of the physiological impact provided, and how this impact is individually perceived during and after physical exercise, define subsequent human behavior and its potential relationship with adherence to training [2]. The individual understanding of affective responses can be characterized as positive, that is, the perception of stimuli provided well-being and tranquility, and generally reduced tension, or negative, where the brain perceives the offered stimulus as a stressor mechanism, increasing the state of anxiety and tension [3]. We currently know that, primarily, high-intensity interval exercises are being prioritized for training prescriptions within major training centers and gyms [4, 5] However, while such a mode of exercise can exert potential benefits and rapid physiological changes, when used indiscriminately, it can provide negative affective responses and a possible strain in the practitioners’ relationship with physical exercise. A possible solution to this impasse seems to be the self-selection of work speeds by the participants themselves. In this case, no matter how much they are asked and encouraged to take on a high workload, the mere perception of non-imposition and self-regulation can modulate differentiated affective responses, inducing positive interpretations. Despite the empirical nature of this theory, such phenomena still need to be more thoroughly investigated.